1 Digest of the Laws of the State of Florida, From the Year One Thousand Eight Hundred and Twenty-Two, to the Eleventh Day of March, One Thousand Eight Hundred Eighty-One Inclusive 873 (James F. McClellan ed., 1881). - (:unkn) unknown (My University, 1881)
Fla. ch. 174, § 24, item 14: Replaced the two hundred dollar annual tax for vendors and ten dollar tax for open carry with a fifty dollar occupational license for vendors of pistols, Bowie-knives, or dirk-knives.
Keywords: LICENSE - DEALERS